More Effective Consolidation of Episodic Long‐Term Memory in Children Than Adults—Unrelated to Sleep. Issue 5 (8th June 2017) - Wang, Jing‐Yi; Weber, Frederik D.; Zinke, Katharina; Inostroza, Marion; Born, Jan
Abstract : Abilities to encode and remember events in their spatiotemporal context (episodic memory) rely on brain regions that mature late during childhood and are supported by sleep. We compared the temporal dynamics of episodic memory formation and the role of sleep in this process between 62 children (8–12 years) and 57 adults (18–37 years). Subjects recalled "what–where–when" memories after a short 1‐hr retention interval or after a long 10.5‐hr interval containing either nocturnal sleep or daytime wakefulness. Although children showed diminished recall of episodes after 1 hr, possibly resulting from inferior encoding, unlike adults, they showed no further decrease in recall after 10.5 hr. In both age groups, episodic memory benefitted from sleep. However, children's more effective offline retention was unrelated to sleep.